2019
DOI: 10.2106/jbjs.18.00624
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibrinogen Exhibits Better Performance Than Plasma D-Dimer in the Diagnosis of Periprosthetic Joint Infection

Abstract: Background: The search for potential markers for a timely and accurate diagnosis of periprosthetic joint infection (PJI) is ongoing. Previous studies have focused on inflammatory markers and have rarely examined coagulation-related indicators. The purpose of this study was to evaluate the values of plasma fibrinogen, D-dimer, and other blood markers for the diagnosis of PJI through a multicenter retrospective study. Methods: A total of 565 revision tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
184
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(205 citation statements)
references
References 25 publications
18
184
2
1
Order By: Relevance
“…In comparison, D-dimer had much lower values of 64.5% sensitivity and 65.0% specificity [49]. D-dimer, when combined with other biomarker tests, is seen to have an increase in specificity, because D-dimer on its own had sensitivity and specificity values of 67.44% and 44.09%.…”
Section: Biomarkersmentioning
confidence: 90%
See 1 more Smart Citation
“…In comparison, D-dimer had much lower values of 64.5% sensitivity and 65.0% specificity [49]. D-dimer, when combined with other biomarker tests, is seen to have an increase in specificity, because D-dimer on its own had sensitivity and specificity values of 67.44% and 44.09%.…”
Section: Biomarkersmentioning
confidence: 90%
“…Fibrinogen has been found to be a more promising marker with sensitivity and specificity similar to that of traditional inflammatory markers. Plasma fibrinogen sensitivity and specificity range from 76.3-81.0% and 25.0-86.2%, respectively [49,50]. Plasma fibrinogen has even been shown to have sensitivity as high as 90% when the threshold was lowered to 519 mg/dL, but the specificity of the test still suffered, reaching only 34% [50].…”
Section: Biomarkersmentioning
confidence: 99%
“…Besides, the value of fibrinogen and ESR had the tendency to be significance. This is no surprisingly given that the utility and threshold of the four serum markers had been thoroughly studied [16,22,27,28]. However, at the time of reimplantation, values of CRP and fibrinogen were significant higher in re-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) was proved to be useful in diagnose PJI [12][13][14], and Hoell et al reported the good utility of IL-6 in predicting failure of reimplantation [15]. Li et al reported fibrinogen had good performance in diagnosis of PJI [16]. However, more research is needed to determine the accuracy and reliability of these serum indicators in predicting the proper timing of reimplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) was suggested to be useful in diagnosing PJI [12][13][14], and Hoell et al reported the high utility of IL-6 in predicting reimplantation failure [15]. Li et al reported that fibrinogen had good performance in the diagnosis of PJI [16]. However, more research is needed to determine the accuracy and reliability of these serum indicators for predicting the proper timing of reimplantation.…”
Section: Introductionmentioning
confidence: 99%